Aktivitas Antioksidan Sediaan Lipstik Kombinasi Ekstrak Buah Naga Merah dan Umbi Bit - Regia Desty Rakhmayanti; Rini Tri Hastuti; Pradea Indah Lukito (Jurnal Kebidanan dan Kesehatan Tradisional, 2020)
Background: The National Agency of Drug and Food Control of Republic Indonesia (BPOM) report in 2016 showed that 43 cosmetics contains hazardous ingredients such as synthetic red dye K3 and K10. The use of synthetic dyes can cause poisoning, cancer and accelerate aging. Some plants that contain natural dyes are red dragon fruit (Hylocereus polyrhizus)and beetroot (Beta vulgaris L.). Red dragon fruit contains betalain color pigment which can be used as natural coloring agent and has antioxidant activity. The red-purple pigment in beetroot is a derivative of betacyanin and betanin which has antioxidant activity. Methods: This study used red dragon fruit and beetroot which was formulated into lipstick formula and determine the antioxidant activity with DPPH method using spectrophotometer UV-Vis. Results: The organoleptic test of lipstick formula 1-5 showed maroon to pink color and control formula was white. The lipstick smells like chocolate. The homogenity test showed that all of the formula was homogeneous. The smear test showed that formula 1-5 was transparent maroon to pink and control formula was colorless. The pH value of all formula was 5. The melting point was F1 (63,7°C), F2 (64,3°C), F3 (64,2°C), F4 (64,5°C) and control (64°C). The breaking point of all formula was F1 (166,7 gram), F2 (170 gram), F3 (163,3 gram), F4 (166,7 gram), F5 (170 gram) and K (170 gram). The result of antioxidant activity test showed that IC50 of all formula was F1 (12,6 ppm), F2 (13,99 ppm), F3 (13,29 ppm), F4 (13,33 ppm) dan F5 (14,17 ppm). This means that the lipsticks has a very strong antioxidant activity. The SPPS test showed there are no different between all the formula with significant value 0,07-0,9>0,05. Conclusion: The lipstick that was made fulfilled the physical test requirements and has a very strong antioxidant activity with IC50 levels > 50 ppm.